Effect of Think Talk Write (TTW) Model with Lagari Media on Primary Students’ Literacy and Communication Skills - Solichah, Mar'atus; Supriyono, Supriyono; Rachmiazasi Masduki, Lusi (STAI Miftahul Ula Nganjuk, 2025)
This study investigated the effect of the Think Talk Write (TTW) learning model combined with serialized picture screen media, known as Lagari, on the literacy and communication skills of third-grade students in an Indonesian elementary school. Employing a quantitative approach with a quasi-experimental design, the research involved a specific sample of primary school learners to measure the impact of this integrated method. The findings from statistical analyses, including the independent sample t-test and linear regression, were decisive. The results showed a significance value of 0.000 (p < 0.05), clearly indicating that the TTW model with Lagari media (X) had a significant positive effect on both students' reading and writing literacy skills (Y1) and their communication abilities (Y2). The rationale for this success is rooted in the model's structured yet interactive nature. The TTW framework actively engages students by first requiring them to process information individually (Think), then articulate and debate their ideas within a group setting (Talk), and finally construct and solidify their understanding through written expression (Write). This entire process is effectively scaffolded by the Lagari media, which provides a coherent visual narrative that stimulates discussion and guides narrative construction. The implications of these findings are substantial for educational practice. They confirm that the TTW model, when enhanced with visual aids like Lagari, is a highly effective pedagogical strategy. It is therefore strongly recommended for application in primary education to simultaneously cultivate the critical and interconnected competencies of literacy and verbal communication, which are fundamental to academic success and lifelong learning